Forms, function, and use of early eneolithic pottery and settlement structures from Zgornje Radvanje, Slovenia - Kramberger, Bine (Documenta Praehistorica, 2015)
Taking milk as a point of departure, we set out on a journey to explore the 'mutual be- comings' of different bodies, species, and things. We argue that milk should be understood as a component in an assemblage that connects animals, humans, hormones, enzymes, bacteria, food, genes, technologies and material culture. These complex entanglements produced new, unexpected results and effects. Since they form part of this assemblage, all its components are profoundly changed. Focusing on this diversity of relations between humans, other creatures, things and substances is a key to an archaeology that does not radically separate humans and nonhumans.
Keywords: arheološka najdišča; ceramic; eneolitik; keramika; lončarstvo; Maribor; naselja; prazgodovina; Radvanje; Slovenia; Slovenija